The Bauman reader - Beilharz, Peter (Blackwell Publishers, 2001)
The remarkably diverse writings of Zygmunt Bauman range across a large number of issues in sociology, politics, history, and cultural studies. This is the first collection of Bauman's writings to cover the entire breadth of his work, and includes a summarizing essay and commentary by editor Peter Beilharz. Beginning with Bauman's early English-language work on socialism, the Reader proceeds through Legislators and Interpreters to Bauman's defense of a sociology of the postmodern. The editor has also selected essays from Bauman's preeminent works on the Holocaust and on globalization. The book includes a new extensive interview, anticipating some of Bauman's forthcoming work.